2006
DOI: 10.1681/asn.2005070698
|View full text |Cite
|
Sign up to set email alerts
|

Treatment with an Inhibitory Monoclonal Antibody to Mouse Factor B Protects Mice from Induction of Apoptosis and Renal Ischemia/Reperfusion Injury

Abstract: Complement activation in the kidney after ischemia/reperfusion (I/R) seems to occur primarily via the alternative complement pathway. The ability of an inhibitory mAb to mouse factor B, a necessary component of the alternative pathway, to protect mice from ischemic acute renal failure was tested. Treatment with the mAb prevented the deposition of C3b on the tubular epithelium and the generation of systemic C3a after renal I/R. Treated mice had significantly lower increases in serum urea nitrogen and developed … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

10
87
2

Year Published

2007
2007
2023
2023

Publication Types

Select...
4
3
1

Relationship

2
6

Authors

Journals

citations
Cited by 118 publications
(99 citation statements)
references
References 30 publications
10
87
2
Order By: Relevance
“…4 In agreement with these observations, the use of complement inhibitors was effective in limiting ischemia-reperfusion damage in normal animals. 9,10 These data strongly suggest that the inhibition of complement may represent a potential target for preventing tissue damage. 6,11 Interestingly, data available so far indicate that, in contrast to ischemia-reperfusion in the intestine, heart, and lung, complement activation due to ischemia-reperfusion in kidneys occurs almost exclusively through the alternative pathway.…”
Section: Discussionmentioning
confidence: 92%
See 1 more Smart Citation
“…4 In agreement with these observations, the use of complement inhibitors was effective in limiting ischemia-reperfusion damage in normal animals. 9,10 These data strongly suggest that the inhibition of complement may represent a potential target for preventing tissue damage. 6,11 Interestingly, data available so far indicate that, in contrast to ischemia-reperfusion in the intestine, heart, and lung, complement activation due to ischemia-reperfusion in kidneys occurs almost exclusively through the alternative pathway.…”
Section: Discussionmentioning
confidence: 92%
“…8 Moreover, the use of anti-factor B or C5a-receptor antagonists has been shown to reduce renal damage due to ischemia-reperfusion. 9,10 Therefore, prevention of complement activation is currently considered one of the best therapeutic targets to prevent or limit ischemia-reperfusionϪinduced renal damage. 5,6,11 C1-inhibitor (C1INH) is a potent inhibitor of proteases of the classical and lectin complement pathways (C1r, C1s, and MASP2).…”
mentioning
confidence: 99%
“…To accommodate for variation in the response to serum batches, direct comparisons are only made between cells treated side by side with the same serum batch. We have previously demonstrated that under these conditions the cells do not undergo a significant degree of spontaneous complement-mediated lysis (21), and pilot experiments demonstrated that when exposed to this concentration of serum, the transcription of the target genes increased after 1 h. To explore the pathways by which serum elicits production of the chemokines by these cells, the alternative pathway was blocked in the serum using the highly inhibitory mouse anti-mouse factor B mAb 1379 (0.5 g/l) (27) in medium containing 10% serum. To block specific complement activation fragments, the cells were treated with a small molecule (5 or 50 M of SB290157; Calbiochem).…”
Section: In Vitro Assay Of Ptec Response To Complement Activationmentioning
confidence: 98%
“…For example, hypoxic PTECs synthesize C3 and express decreased complement inhibitory proteins on their basal surface (20). Once activated, the complement system generates the C3a and C5a anaphylatoxins, and systemic levels of C3a are measurably increased in mice after renal I/R (21). Complement activation fragments may induce cells to produce a number of cytokines and chemokines (6,22,23).…”
Section: Schemia/reperfusion (I/r)mentioning
confidence: 99%
“…It has been previously demonstrated that factor B is an important mediator of tissue damage in the setting of a number of autoimmune disorders, because mice deficient in factor B are protected from inflammation and tissue destruction in several animal models of autoimmunity (14)(15)(16)(17)(18)(19). Previous work has also shown that factor B plays an important role in the pathogenesis of I/R injury (20,21). Factor B-deficient mice developed less C3 deposition, neutrophil infiltration and functional impairment in comparison to wild-type (WT) counterparts in a renal I/R model (20).…”
Section: Introductionmentioning
confidence: 99%